A Novel Mobile Phone Text Messaging Platform Improves Collection of Patient-Reported Post-operative Pain and Opioid Use Following Orthopedic Surgery. Issue 1 (February 2019) - Premkumar, Ajay; Lovecchio, Francis C.; Stepan, Jeffrey G.; Kahlenberg, Cynthia A.; Blevins, Jason L.; Albert, Todd J.; Cross, Michael B.
Background: Prospective collection of patient-reported opioid consumption and pain levels post-surgically may hold value in highlighting solutions related to the opioid crisis. Traditional methods for collecting patient-reported outcomes after surgery, such as paper surveys, often have poor response rates, and electronic messaging may offer more convenience and therefore yield more robust data. Questions/Purposes: The purpose of this study was to evaluate whether a novel mobile phone short message service (SMS) platform would lead to better patient response rates to surveys on pain and opioid use than data-collection tools. Methods: An SMS text messaging platform was created and implemented between September 2017 and May 2018 at an orthopedic specialty hospital. The purpose was to collect reports on opioid consumption and pain levels twice a day for 6 weeks post-surgery from patients who had undergone total hip or knee arthroplasty or a single-level lumbar microdiscectomy or decompression spine surgery. Patients who responded to fewer than 50% of the text messages were excluded. Results: Our mobile phone text messaging platform was used by 183 patients, demonstrating a significantly higher response rate (96.1%) than our institution's post-operative email registry capture, as well as the majority of published response rates for post-operative outcomes captured through electronic and traditional data-collection systems. Response rate remained consistently high among the various surgeons and across patients, regardless of age. Conclusions: This application of a widely available technology can improve the measurement of post-operative patient-reported outcomes. Such data can in turn be used in the development of strategies to reduce post-operative opioid use. The adoption of novel technologies at a patient level will play a key role in combating the opioid epidemic.